2022
DOI: 10.1002/hpm.3492
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and challenges of using health information technology in home care: A systematic review

Abstract: Objective: Despite the benefits of applying Information technology (IT) in-home care some challenges may affect the quality of the services. To deal with these challenges, it is required to identify them before providing such services.Therefore, the aim of this study is to systematically determine the challenges and barriers of using health IT in-home care. Moreover, the possible solutions reported in the included studies were examined. Materials and Methods: We performed a systematic search of the PubMed, Web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…The author employed telehealth for postoperative patients, patients undergoing follow‐up for orthopaedic disorders in outpatient clinic. Findings from Tanaka et al 32 . reported that the use of telehealth for orthopaedic treatment in Norway was shown to be cost‐effective.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The author employed telehealth for postoperative patients, patients undergoing follow‐up for orthopaedic disorders in outpatient clinic. Findings from Tanaka et al 32 . reported that the use of telehealth for orthopaedic treatment in Norway was shown to be cost‐effective.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…more inclusive videos and online training programs exist for health practitioners. These helps to provide exposure to telehealth methods as employed by Texas A&M University and the University of Redlands which provide training about topics like Telehealth 101, laws and ethics of telehealth, and multicultural aspects of rural health 32 . Furthermore, Tanaka et al 33 .…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Galavi et al conducted a systematic review of barriers to the adoption of health technology solutions in home care. 25 They found that significant barriers to entry for patients included such factors as lack of digital literacy, difficulty of use by older adults, forgetfulness, and complexity of existing comorbidities. 25 Lo et al, in a qualitative study also identified the apparent absence of a physician's involvement as a primary concern of patients considering the use of an artificial intelligence-enabled system.…”
Section: Discussionmentioning
confidence: 99%